Relict oak forest of Quercus greggii (A. DC.) Trel. in the Potosino Plateau, Mexico (Agro Productividad, 2025)
Objective: Quercus greggii (A. DC.) Trel. is a representative species of the shrubby oak forest, ecologically important and poorly studied. Its presence was identified, characterized, quantified, and its distribution area determined on Peñón Blanco Hill, Salinas, San Luis Potosí, Mexico.Design/methodology/approach: Samples of Quercus specimens were collected and identified using dichotomous keys. Representative anatomical structures of the leaves were revealed through clearing techniques, venation was studied, and the stomatal index of each individual was calculated. The distribution of Q. greggii (n=25) was estimated by georeferencing each individual, projected onto orthophotos, and limited to 2.44 hectares. Results: The sampled trees were adults, with an average height of 7.5 ± 1.8 m, diameters ranging from 4.6 ± 1.8 m at breast height (DBH) and 5.0 ± 2.7 m in canopy coverage (CC). The canopy area was 85.30 ± 67.6 m², and the breast height area was 397.5 ± 0.027 cm². The average stomatal index was 4.8 ± 1.3.Findings/conclusions: The described population of Q. greggii is isolated, and the low rate of regeneration along with overgrazing in the area could pose a threat to its survival. Therefore, it is necessary to enhance knowledge about this species at the site to establish a management plan that ensures its long-term persistence.